2020
DOI: 10.1111/cas.14403
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal expression of trefoil factor‐1 and thyroid transcription factor‐1 in lung adenocarcinomas

Abstract: Molecular targeted therapies against EGFR and ALK have improved the quality of life of lung adenocarcinoma patients. However, targetable driver mutations are mainly found in thyroid transcription factor‐1 (TTF‐1)/NK2 homeobox 1 (NKX2‐1)‐positive terminal respiratory unit (TRU) types and rarely in non‐TRU types. To elucidate the molecular characteristics of the major subtypes of non‐TRU‐type adenocarcinomas, we analyzed 19 lung adenocarcinoma cell lines (11 TRU types and 8 non‐TRU types). A characteristic of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Normally, TFF1 exerts physiological functions by binding to MUC5AC mucin, its corresponding receptors, or transporters. The promotion of cell migration is an important procedure in the process of gastric mucosal repair and reconstruction [ 26 ]. TFF1 plays an important role in promoting cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…Normally, TFF1 exerts physiological functions by binding to MUC5AC mucin, its corresponding receptors, or transporters. The promotion of cell migration is an important procedure in the process of gastric mucosal repair and reconstruction [ 26 ]. TFF1 plays an important role in promoting cell migration.…”
Section: Discussionmentioning
confidence: 99%
“… 42 There was also one report on lung AC that appears inconsistent with our current findings, showing that knockdown of TFF-1 inhibited cell proliferation and induced apoptosis in a TFF-1/high and KRAS- mutated lung AC cell line. 43 Again, these overall diverse effects of TFF-1 on cancer cell phenotypes may reflect a complex machinery that varies with cell type. Although discrepancies among these overall results may derived from differences in the cell lines or experimental procedures used (for example, forced expression or knockdown, constitutive or transient overexpression), the functional involvement of TFF-1 in proliferation, migration, invasion and apoptosis, seems much more dependent on upstream events.…”
Section: Discussionmentioning
confidence: 99%
“…These peptides have important functionalities, including interactions with the immune system, involvement in mucosal protection and repair, as well as in tumorigenesis. [36][37][38] Certain interactions at the structure and function levels between the GKN and TFF families were also identified. Previous reports showed that GKN2 could bind with TFF2, 39 as well as TFF1 at a protein level.…”
Section: Discussionmentioning
confidence: 99%